Quantitative OCT Angiography of the Retinal Microvasculature and the Choriocapillaris in Myopic Eyes - Al-Sheikh, Mayss; Phasukkijwatana, Nopasak; Dolz-Marco, Rosa; Rahimi, Mansour; Iafe, Nicholas A.; Freund, K. Bailey; Sadda, SriniVas R.; Sarraf, David (Investigative ophthalmology & visual science, 2017)
To study the retinal capillary microvasculature and the choriocapillaris (CC) in myopic eyes using quantitative optical coherence tomography angiography (OCTA) analysis. Macular OCTA images of 3 × 3 mm were obtained using the RTVue-XR Avanti with AngioVue. Quantitative measurements of the retinal capillary microvascular layers and the CC were analyzed using en face projection images. Vessel density and fractal dimension of the superficial and deep retinal capillary plexus, and area and density of flow reduction in the CC were analyzed, quantified, and compared with an age-matched control group. Fifty eyes with myopia and 34 age-matched healthy eyes were included in this study. The vessel density and the vessel branching complexity using fractal dimension of the retinal capillary microvasculature were significantly lower in myopic eyes (P < 0.001 and P = 0.001). The total number of flow voids in the CC was lower (108.93 vs. 138.63, P = 0.001) but the total and average flow void area was significantly higher (total area 3.715 ± 0.257 vs. 3.596 ± 0.194 mm2, P = 0.026; average area 0.044 ± 0.029 vs. 0.028 ± 0.010 mm2, P = 0.002) compared with the healthy control group. Average choroidal thickness was lower in the myopic group versus the normal control cohort (123.538 ± 73.477 vs. 246.97 ± 41.745 μm, P < 0.05) and significantly reduced in eyes with lacquer cracks (LC) compared with myopic eyes without LC formation (P = 0.003). There was no correlation between choroidal thickness and quantitative parameters of the CC in the myopic eyes. The density of the retinal capillary microvasculature is reduced and the area of flow deficit in the CC is increased in eyes with greater myopia. The relevance of microvascular alterations in the setting of myopia warrants further study.